Zoneamento ecológico-econômico e biodiversidade: contribuição metodológica. Estudo na Bacia e Delta do Rio Parnaíba-Brasil - Matteo, Katia Castro de (2007)
The theme of this current subject concerns the relation between Ecological-Economical Zoning (EEZ) and the biodiversity s protection. For so, an incursion is necessary concerning this important territorial planning tool, with the presentation of its backgrounds, current situation, methodological evolution, main projects already made in the country, with analyses of its biotical aspects data and main products. The research proposes a methodological contribution to the Ecological-Economical Zoning, through the insertion of the biodiversity parameter in two levels of execution: a more strategic level, the Macrozoning, and a more operational vision, the EEZ on local and state scale. The case studied embodies the Parnaíba River Watershed, detailed of the EEZ from the region of Parnaíba River Delta, localized on the states of Piauí, Ceará and Maranhão. The main objective of this study consists in contributing with the Ecological-Economical Zoning methodology in relation with the biotical aspects, improving the insertion of biodiversity on the operational processes. For so, it was opted to get and analyze concerning the biotical environment, as many zoning projects ever made in Brazil as possible, on a 1:250.000 scale or bigger, besides presenting insertion alternatives of the biodiversity theme on different information treating scales, guaranteeing that the biodiversity conservation gets considered on an effective way on the operational procedures of zoning, proposing its thematically integration and supported use of the natural resources. The execution of the work was based mainly on the use of geoprocessing tools, through the reunion of data and information on Geographical Information Systems, using Spring software and ArcGis, with divulgation of the Geographical Data Bank constructed from the secondary data given by the Sustained Development Political Secretary from the Environment Ministry (SDS/MMA) e specific processes made on this study.